Effect of storage time on physicochemical, sensorial, and antioxidant characteristics, and composition of mango (cv. Azúcar) juice (2017)
ABSTRACT: Mango is one of the most popular fruits and a good source of antioxidants compounds. In this study, we monitor the stability of physicochemical and sensory characteristics, antioxidant activity and content of carotenoids and polyphenols of ripe mango cultivar Azúcar stored up to 60 days at - 20°C. All analyses were carried out in mango juice prepared using pulp stored during 1, 8, 30, 44 and 60 days. The sensory analysis was carried out by 200 untrained panelists and juices B and D had the highest scores in all attributes followed by juice C. Physicochemical characteristics were measured by official methods (Association of official analytical chemists) and they were similar through different storage time except for calories and total carbohydrates. Total carotenoids, flavonoids and polyphenols content were measured by colorimetric methods. Polyphenols content was similar over time, meanwhile carotenoids and flavonoids content increased after 8 days of storage and they decreased after 30 days of storage. Antioxidant activity was measured by DPPH (2,2-diphenyl-1-picrylhydrazyl) radical, ABTS (2,2 ́-azino-bis-3-ethylbenzthiazoline-6-sulfonic acid) radical and hydrophilic ORAC (oxygen radical absorbance capacity) method. Juice prepared after 8 and 30 days of mango storage showed the highest antioxidant activity in almost methods. In conclusion, juice prepared from ripe mango cultivar Azucar had similar physicochemical characteristics, sensory characteristics, total phenolic content and antioxidant activity between 1 and 30 days of storage at −20°C.